RADI-01. DIAGNOSTIC ACCURACY AND ADDED VALUE OF QUALITATIVE RADIOLOGICAL REVIEW OF 1H-MRS IN EVALUATION OF CHILDHOOD BRAIN TUMORS. Issue 2 (22nd June 2018) - Manias, Karen; Gill, Simrandeep; MacPherson, Lesley; Oates, Adam; Pinkey, Benjamin; Davies, Paul; Zarinabad, Niloufar; Davies, Nigel; Babourina-Brooks, Ben; Wilson, Martin; Peet, Andrew
Abstract: BACKGROUND: 1 H-Magnetic Resonance Spectroscopy (MRS) facilitates non-invasive diagnosis of pediatric brain tumors through providing metabolite profiles. Prospective studies of diagnostic accuracy and comparisons with conventional Magnetic Resonance Imaging (MRI) are lacking. AIM: To evaluate diagnostic accuracy of qualitative radiological review of MRS for childhood brain tumors, and determine added clinical value compared with conventional MRI. METHODS: Children presenting to a Tertiary Pediatric Centre with brain lesions from December 2015-17 were eligible for inclusion. MRI and single-voxel MRS were acquired on 52 tumors and sequentially interpreted by three radiologists, blind to histopathology. Proportions of correct diagnoses and inter-rater agreement at each stage were compared. Cases were reviewed to determine added value through increased certainty of correct diagnosis, reduced number of differentials, or diagnosis following spectroscopist evaluation. Final diagnosis was agreed by the Tumor Board (TB) at study end. RESULTS: Radiologists' principal MRI diagnosis was correct in 69%, increasing to 77% with MRS. MRI+MRS resulted in significantly more additional correct diagnoses than MRI alone (p=0.035). There was significant increase in inter-rater agreement when correct with MRS (p=0.046). Added value following radiologist interpretation of MRS occurred in 73% of cases, increasing to 83% with additional spectroscopist review. First histopathological diagnosis was available a median 9.5 days following imaging, with 25% of all patients managed without conclusive histopathology. CONCLUSION: MRS can improve accuracy of non-invasive diagnosis of pediatric brain tumors and add value in the diagnostic pathway. Incorporation into practice has potential to facilitate early diagnosis, guide treatment planning and improve patient care.